2004
DOI: 10.1046/j.1600-6135.2003.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Low-Dose TBI or DST Overcomes CD8+ T-Cell-Mediated Alloresistance to Allogeneic Marrow in Recipients of Anti-CD40L

Abstract: Treatment with a single injection of anti‐CD40L (CD154) monoclonal antibody (mAb) and fully mismatched allogeneic bone marrow transplant (BMT) allows rapid tolerization of CD4+ T cells to the donor. The addition of in vivo CD8 T‐cell depletion leads to permanent mixed hematopoietic chimerism and tolerance. We now describe two approaches that obviate the requirement for CD8 T‐cell depletion by rapidly tolerizing recipient CD8 T cells in addition to CD4 cells. Administration of donor‐specific transfusion (DST) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 52 publications
1
67
0
Order By: Relevance
“…The combination of anti-CD154 monoclonal antibodies and allo-HCT tolerizes existing alloreactive CD4 + T cells in the periphery by anergy followed by deletion, owing to presentation of donor antigens on APCs in the absence of a CD40-mediated activation signal 34 . Donor-reactive CD8 + T cells also undergo deletion in the periphery, even more rapidly than CD4 + T cells in this model 36 (Y. Takeuchi et al, unpublished observations), by mechanisms that are currently under investigation.…”
Section: Anergy and Deletion Of Peripheral Auto-and Alloreactive T Cellsmentioning
confidence: 74%
“…The combination of anti-CD154 monoclonal antibodies and allo-HCT tolerizes existing alloreactive CD4 + T cells in the periphery by anergy followed by deletion, owing to presentation of donor antigens on APCs in the absence of a CD40-mediated activation signal 34 . Donor-reactive CD8 + T cells also undergo deletion in the periphery, even more rapidly than CD4 + T cells in this model 36 (Y. Takeuchi et al, unpublished observations), by mechanisms that are currently under investigation.…”
Section: Anergy and Deletion Of Peripheral Auto-and Alloreactive T Cellsmentioning
confidence: 74%
“…11 Responder and irradiated stimulator splenocytes (8 ϫ 10 5 each) were coincubated for 5 days, after which serial 2-fold dilutions were prepared. Target cells were incubated with concanavalin A (2 g/mL) for 2 days, then labeled with 51 Cr (1 Ci/mL) and incubated for 4 hours with responders.…”
Section: Cell-mediated Lympholysis Assaymentioning
confidence: 99%
“…In the mouse model, a minimal protocol that uses low-dose (3 Gy) total body irradiation (TBI) and costimulatory blockade with anti-CD154 (CD40 ligand) monoclonal antibody (mAb) together with bone marrow transplantation (BMT) has reliably induced stable mixed chimerism and permanent survival of MHC-mismatched skin grafts. 11 In this model, alloreactive CD4 and CD8 cells are both independently capable of rejecting BM. The mechanistic study of Fehr et al 12 has demonstrated that the tolerance of donorspecific peripheral T cells involves very rapid unresponsiveness followed by clonal deletion.…”
Section: Introductionmentioning
confidence: 97%
“…A growing body of the literature suggests that inhibition of Tcell function using TCD mAb and/or co-stimulatory blockade is fundamental for engraftment of allogeneic hematopoietic cells (12,24,25,29,(31)(32)(33). However, such approaches nonspecifically inhibit T-cell dependent immunity, including the regulatory mechanism that is important for establishment of tolerance.…”
Section: Discussionmentioning
confidence: 99%